Kesulitan Belajar Siswa Dalam Pembelajaran Daring Pada Pokok Bahasan Hidrokarbon - Lamtiar Ferawaty Siregar; Nurlela - Pandiangan; Novike Bela Sumanik (PendIPA Journal of Science Education, 2021)
Online learning requires students and teachers to communicate interactively by utilizing information and communication technology, such as computer media with the internet, cellphones, videos. Hydrocarbons are an abstract subject matter of chemistry, involving concepts, using molecular models of one kind or another to describe molecules in three dimensions. This study aims to determine the difficulties of students in online learning the subject of hydrocarbons. This research is a descriptive study with the instrument used 15 item questions and a questionnaire of 20 items. Students have difficulty answering the problem of determining the primary, secondary, tertiary C atom; IUPAC nomenclature for alkanes, alkenes, alkenes; and reactions to hydrocarbons. Online learning on the subject of hydrocarbons is not enough to use an android cellphone, but requires a laptop, computer or notebook. Student interest and motivation are very much needed in independent learning to be the key to the success of online learning.